Prioritizing National Happiness - Larry Hufford (Revista Espaço Acadêmico, 2021)
In 1972 Bhutan, one of the materially poorest nations in the world, initiated a new leader, King Jime Singye Wanachuck. The new King, now 50 years old, had observed that new nation-states in the “developing world” were all focused on economic growth and trade, that is, gross domestic product (GDP). Bhutan’s King, analyzing the country’s unique culture founded in Buddhist spiritual values, decided to focus his nation’s priority not on its GDP but GNH, or gross national happiness.